Narrowband Light Reflection Resonances from Waveguide Modes for High-Quality Sensors - Gu, Ping (Nanomaterials (Basel), 2020)
Designing various nanostructures to achieve narrowband light reflection resonances is desirable for optical sensing applications. In this work, we theoretically demonstrate two narrowband light reflection resonances resulting from the excitations of the zero-order transverse magnetic (TM) and transverse electric (TE) waveguide modes, in a waveguide structure consisting of an Au sphere array on an indium tin oxide (ITO) spacer on a silica (SiO(2)) substrate. The positions of the light reflection resonances can be tuned easily, by varying the array periods of gold (Au) spheres or by changing the thickness of the ITO film. More importantly, the light reflection resonances have a very narrow bandwidth, the full width at half maximum (FWHM) of which can be reduced to only several nanometers for the zero-order TM and TE waveguide modes. The conventionally defined performance parameters of sensors, sensitivity (S) and figure of merit (FOM), have quite high values of about 80 nm/RIU and 32, respectively, in the visible wavelength range.